The subject of coexistence : otherness in international relations - Odysseos, Louiza (Borderlines (Minneapolis, Minn.), 2007)
Louiza Odysseos argues that debates about ethnic conflict, human rights, and the viability of multicultural communities all revolve around the question of coexistence. She traces the institutional neglect of coexistence to the ontological commitments of international relations as predicated on conceptions of modern subjectivity. Here, Odysseos opens up the possibility of a coexistential ontology in which selfhood can be rethought beyond subjectivism.